Reconstruction of the Restorative Justice Paradigm in the Indonesian Criminal Justice System: A Standardized Formulation Based on Sharia Maqashid - Abdul Rahman; Watni Marpaung; Arifuddin Muda Harahap (Program Pascasarjana IAIN Langsa, 2026)
The implementation of restorative justice within the Indonesian criminal justice system has developed significantly as a shift from a retributive approach toward a justice paradigm oriented toward recovery. However, its implementation still faces fundamental problems, including fragmented regulations, inconsistent standards among law enforcement institutions, and the absence of a comprehensive national framework that ensures legal certainty and uniform application. This study aims to analyze the problems of restorative justice implementation and formulate a reconstruction of restorative justice standardization within the Indonesian criminal justice system based on maqashid syariah. This research employs normative legal research using statutory, conceptual, and philosophical approaches. The findings demonstrate that restorative justice standardization is essential to integrate the principles of legal certainty, victim protection, offender accountability, and social restoration. The maqashid syariah perspective provides a philosophical foundation that restorative justice should be directed toward achieving public benefit (maslahah), preventing harm (mafsadah), and protecting fundamental human values. The contribution of this research lies in proposing a national restorative justice standardization model that integrates modern criminal justice objectives with substantive justice principles based on maqashid syariah as a direction for criminal justice reform in Indonesia. Theoretically, this model expands the conceptual foundation of restorative justice by integrating maqashid syariah with contemporary principles of criminal justice, particularly in balancing legal certainty, victim-oriented justice, accountability, and social restoration. Practically, the proposed standardization can serve as a reference for law enforcement institutions in developing consistent procedures and criteria for restorative justice implementation while strengthening victim protection and offender accountability. From a policy perspective, the findings support the development of an integrated national framework for restorative justice that harmonizes regulations and institutional practices across the Indonesian criminal justice system, thereby promoting greater consistency, legal certainty, and substantive justice.